Changes in arterial blood gases during endoscopy in patients with chronic obstructive lung disease - Yıldıran SONGÜR,; Nejla SONGÜR,; Himmet KARACA,; Ayşe ÖZSÖZ,; Sadun KOŞAY, (Turkish Journal of Gastroenterology, 2020)
-